Be Wary of Passive Resistance to Health Information Systems - Kasiati, Klanting (Health Notions, 2017)
Implementation of health information systems (HIS) has resulted in multiple duties for health professionals as health care workers and HIS operators. This dual task can lead to increased effort for them, which can lead to resistance to HIS, either actively or passively. Both must be handled seriously because it often leads to the failure of HIS implementation. Meanwhile, passive resistance must be cautioned because in the early stages it is usually unknown to managers that it fails to be anticipated and worsens. As a strategic solution, organizations must always maintain and improve organizational support for users.